DETERMINATION OF THE PROXIMATE AND MINERAL CONTENTS OF DESERT DATE KERNEL (BALANITES AEGYPTIACA LINN.) AND THE PHYSICAL AND CHEMICAL CHARACTERISTICS OF THE KERNEL OIL AVAILABLE IN KANO STATE, NIGERIA - Datti, Y.; Yahya, A. T.; Koki, I. B.; Lado, U. A.; Musbahu, L.; Shuaibu, M. M.; Ahmad, U. U.; Adamu, G. A.; Umar, A.; Nura, T. (FUDMA Journal of Sciences, 2020)
The desert date (Balanites aegyptiaca) is one the most important relish trees found in many African countries. In this study the proximate and mineral compositions of the desert date kernel, as well as some of the physical and chemical properties of its oil were analyzed using standard procedures. The results of the proximate composition revealed the following mean concentrations: Moisture content 3.19%;  ash content 2.89%; fat content 39.63%; crude protein content 33.75%; crude fiber content 13.06% and carbohydrate content 7.48%. And the mineral content revealed the following mean concentrations: Potassium 1.120 (mg/100g); calcium  0.390 (mg/100g); sodium 0.801 (mg/100g); magnesium 0.142 (mg/100g); iron 0.0024 (mg/100g); manganese 0.01512 (mg/100g); zinc 0.0082 (mg/100g); copper 0.00225 (mg/100g); nickel 0.00582 (mg/100g); cobalt 0.002623 (mg/100g) and chromium 0.003224 (mg/100g). While the results for the physical analysis of the kernel oil revealed the following: Color pale yellow; density g/cm3 0.910; specific gravity 0.907; refractive index 1.458 and viscosity 19.68. And on the other hand, the results for the chemical analysis of the kernel oil revealed the following: acid value 3.06 mgKOH/g; free fatty acid 1.27; peroxide value 3.71 mEq/Kg; saponification value 198 mg/KOH/g and iodine value 98.73 100/g. All the results were compared and found to be within the FAO/WHO standards. The seeds kernel of this plant was found to be high nutritional value, while its oil can be a good source of raw material for many oil-based products
Keywords: Proximate composition; Mineral contents; Balanite aegyptiaca; Kernel; Kernel oil